Workshops for Volunteer Tutors of the YABIM PKBM (Center for Community Learning Activities) - Setiyowati, Harlis; Sasmito, Triswati (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
With a focus on "STUDENT EDUCATION AND SERVICE," the "2018 Community Service Activity Program." The practice was conducted at the Depok Integrated Terminal’s Bina Insan Mandiri Foundation (Depok Master School). A qualitative methodology was used during the training and counseling that lasted one month. This activity aims to motivate instructors, lecturers, and students to participate and contribute to the growth and application of care and personality. The performance of volunteer tutors is positively impacted by a teacher’s pride in addition to their involvement in the Tri Dharma of Higher Education through information sharing.